2020
DOI: 10.1371/journal.pone.0241277
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of arthroscopic debridement of massive irreparable rotator cuff tears

Abstract: Objectives To evaluate the clinical and radiographic outcome of low-demand patients with massive rotator cuff tears undergoing arthroscopic debridement in mid- and long-term follow-up, as well as the rate of conversion to reverse shoulder arthroplasty. Methods We performed a retrospective analysis of 19 patients with a mean age at surgery of 68 years (range, 55–80 years) from a previously described consecutive cohort and after a mean follow up of 47 month (FU1) and 145 month (FU2). The functional outcome was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…A total of 6 primary studies for BT (cases series = 2, case–control = 2, randomized control trial = 1, prospective cohort study = 1) [ 15 , 22 , 35 , 36 , 37 , 38 ] involving 441 shoulders demonstrated significant improvements in the CMS at the final follow-up (range, 10.8,28) ( Figure 3 ). The minimum preoperative and maximum postoperative CMS were, respectively, 29.9 and 67.6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 6 primary studies for BT (cases series = 2, case–control = 2, randomized control trial = 1, prospective cohort study = 1) [ 15 , 22 , 35 , 36 , 37 , 38 ] involving 441 shoulders demonstrated significant improvements in the CMS at the final follow-up (range, 10.8,28) ( Figure 3 ). The minimum preoperative and maximum postoperative CMS were, respectively, 29.9 and 67.6.…”
Section: Resultsmentioning
confidence: 99%
“…The minimum preoperative and maximum postoperative CMS were, respectively, 29.9 and 67.6. For BT, 2 studies (cases series = 1, case–control = 1) [ 37 , 39 ] involving 50 shoulders demonstrated significant improvements in the ASES at the final follow-up (range, 30, 45.8).…”
Section: Resultsmentioning
confidence: 99%
“…Irreparable RCT may also be treated by an arthroscopic debridement of the remaining rotator cuff in combination with a (reversed) subacromial decompression (SAD) and a tenotomy or tenodesis of the LHBT ( Table 2 ) [ 21 , 22 , 23 ]. While lesions of the LHBT have been identified as a source of persistent pain that can be resolved with LHBT tenotomy, the purpose of arthroscopic SAD is to create a smooth, non-impinging acromiohumeral articulation by creating space, removing osteophytes and bony irregularities.…”
Section: Arthroscopic Debridement Tenotomy/tenodesis Of the Long Head...mentioning
confidence: 99%
“…Low physical demand, sufficient residual shoulder function, older patient age and pain as the chief complaint are the main indications for arthroscopic debridement combined with (reverse) SAD and LHBT tenotomy/tenodesis. As such, a contemporary study in 19 patients (mean age 68 years) with symptomatic massive RCT reports significant improvements in functional outcomes, with an improvement in ASES Score of more than 30 points and a significant pain relief after arthroscopic debridement with SAD and the tenotomy of the LHBT after a minimum 10-year follow-up [ 23 ]. However, in this cohort 26% of patients failed and underwent RTSA during follow-up, emphasizing the importance of careful patient selection and preoperative counseling [ 23 ].…”
Section: Arthroscopic Debridement Tenotomy/tenodesis Of the Long Head...mentioning
confidence: 99%
“…Разрывы вращательной манжеты с ретракцией сухожилий более 5 см или вовлечение двух или более сухожилий являются массивными повреждениями. Такие повреждения составляют до 10-40% [1].…”
Section: обоснованиеunclassified